The Analysis of Rank Fusion Techniques to Improve Query Relevance - Diyah Puspitaningrum; Jeri Apriansyah Pagua; Aan Erlansari; Fauzi Fauzi; Rusdi Efendi; Desi Andreswari; I.S.W.B. Prasetya (Universitas Ahmad Dahlan, 2015)
Rank fusion meta-search engine algorithms can be used to merge web search results of multiple search engines. In this paper we introduce two variants of the Weighted Borda-Fuse algorithm. The first variant retrieves documents based on popularities of component engines. The second one is based on k user-defined toplist of component engines. In this research, experiments were performed on k=50,100,200 toplist with AND/OR combinations implemented on ‘UNIB Meta Fusion’ meta-search engine prototype which employed 3 out of 5 popular search engines. Both of our two algorithms outperformed other rank fusion algorithms (relevance score is upto 0.76 compare to Google that is 0.27, at P@10). The pseudo-relevance automatic judgement techniques involved are Reciprocal Rank, Borda Count, and Condorcet. The optimal setting was reached for queries with operator